Silence before the Storm – Mycotic Aneurysm in Posttransplant Recipient - G. Praveen; Mohammed Fahad Khan; Rohan Augustine; Vishwanath Siddini; Mahesha Vankalakunti; H Sudarshan Ballal (Indian Journal of Transplantation)
Although vascular complications due to the arterial anastomosis are rare in transplant patients, infectious vascular complications around the anastomosis site that carry a risk of rupture can cause significant mortality and morbidity. Signs and symptoms of any infectious process can be masked in patients taking more potent immunosuppressants at the early period after transplantation. Staphylococcus aureus, Gram-negative bacilli, and fungi such as Candida albicans can especially produce serious complications. We present a case of a renal transplant patient with an arterial anastomosis aneurysm leading to rupture. Early diagnosis may be lifesaving due to the silent and insidious presentation of arterial mycotic aneurysms and their high mortality and morbidity rates.